Proceedings of the 12th Annual International Conference on Mobile Systems, Applications, and Services 2014
DOI: 10.1145/2594368.2594380
|View full text |Cite
|
Sign up to set email alerts
|

Autodirective audio capturing through a synchronized smartphone array

Abstract: High-quality, speaker-location-aware audio capturing has traditionally been realized using dedicated microphone arrays. But high cost and lack of portability prevents such systems from being widely adopted. Today's smartphones are relatively more convenient for audio recording, but the audio quality is much lower in noisy environment and speaker location cannot be readily obtained. In this paper, we design and implement Dia, which leverages smartphone cooperation to overcome the above limitations. Dia supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Due to different oscillator frequencies, the build-in clocks may trigger to sample more or less than 44.1k per second. The synchronization issue imposed by the deviation in microphone sampling rate is a complex research problem studied by various researchers [30,28,15]. Figure 8 shows some observations on the sampling offset distributions.…”
Section: Synchronizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to different oscillator frequencies, the build-in clocks may trigger to sample more or less than 44.1k per second. The synchronization issue imposed by the deviation in microphone sampling rate is a complex research problem studied by various researchers [30,28,15]. Figure 8 shows some observations on the sampling offset distributions.…”
Section: Synchronizationmentioning
confidence: 99%
“…Unfortunately, Apple does not provide the APIs to proactively access more than one microphone in iPhone 5 or 5S. Besides Samsung and iPhone, other smartphones like Nexus 5 are also tested to show a linear relationship between the elapsed time and the number of offset samples [30].…”
Section: Synchronizationmentioning
confidence: 99%
“…Notice that because the nodes are equipped with two microphones, we take the average of the ToAs to obtain the ToA at the center of the array. The specific methods to obtain internode synchronization fall outside the scope of this paper, although there are multiple solutions in the literature, for example, Sur et al [26].…”
Section: Problem Formulationmentioning
confidence: 99%
“…Recent work by Sur, Wei, Zhang [2] and Smeding, Bosma, Castañeda [3] showed that it is definitely possible to implement beamforming solutions in a mobile system. Sur, Wei, and Zhang took a clever approach for handling the synchronizing problem.…”
Section: List Of Figuresmentioning
confidence: 99%
“…Using local timestamps from each of the device's network adapter and creating Linear Regression models around these timestamps, they found an Algebraic solution for synchronizing the devices together. One problem they encountered, however, was that the network adapter's timestamp was not always available in some devices [2]. They also mentioned that you could use an external audio beacon to periodically act as a reference for alignment, but they felt that the beacon would interfere with the recording.…”
Section: List Of Figuresmentioning
confidence: 99%